The development of recreation science as the main theoretical fundamental of tourism integrations - Hladkyi, Olexandr; Mirzodaeva, Tetiana (My University, 2018)
The main factors that effect on the development of recreational activities such as natural, demographic, socio-economic ones as well as social and psychological factors are investigated. The different factors of recreational system economic-geographical location are researched. The different internal factors of recreational activities development are disclosed. The main practical goal of the recreational activities is substantiated.
Keywords: відпочинок; рекреація; основи відпочинку; чинники відпочинку; система відпочинку; дослідження туризму; кафедра туристичного та готельного бізнесу; отдых; рекреація; основы отдыха; факторы отдыха; система отдыха; исследования туризма; recreation; recreolog; recreation fundamentals; factors of recreation; recreation system; tourism investigations